Rehabilitation Including Structured Active Play for Preschoolers With Cancer (RePlay)—Study Protocol for a Randomized Controlled Trial - Pouplier, Anna; Winther, Helle; Christensen, Jan; Schmidt-Andersen, Peter; Zhang, He; Frandsen, Thomas Leth; Schmiegelow, Kjeld; Fridh, Martin Kaj; Larsen, Hanne Bækgaard (Frontiers in Pediatrics, 2022)
Background: Children diagnosed with cancer experience muscle weakness and impaired physical function caused by treatment and related immobility. The situation forces them into a negative cycle of diminished participation in physical and leisure activities and isolation from peers; inhibiting the natural development of social and gross motor skills. This manuscript presents a protocol for a study that explores the effects of using structured active play to maintain preschoolers’ age specific gross motor function and social and personal skills while undertaking intensive cancer treatment. Methods: The study is a two-arm, superiority randomized controlled trial with an intervention and a control group designed to evaluate the effects of a structured active play intervention on gross motor function. Gross motor subtests of the Peabody Developmental Motor Scales, Second Edition (PDMS-2) are used for measurement; with the primary end-point at six months post-treatment initiation. Eighty-four preschool children (aged 1-5 years), newly diagnosed with cancer at the Copenhagen University Hospital are randomly assigned to either an intervention or control group, using 1:1 allocation. The intervention group receives a combined in-hospital and home-based program that includes structured active play activities, while the control group receives standard care, including physiotherapy. During hospital admission, the intervention group undertakes 45-minute structured active play group sessions three times weekly, conducted by exercise professionals. Parents receive training and supervision to facilitate daily individual sessions outside of group sessions. Secondary study outcomes target the children’s overall function level in everyday life, general physical performance, and health-related quality of life. As well, children’s and parents’ experiences within the intervention are explored and the children’s social and personal development is observed. Discussion: Limited evidence exists regarding the effectiveness of rehabilitation interventions, particularly those including active play, for preschoolers diagnosed with cancer. This manuscript reporting on a study protocol will enhance clarity and transparency in reporting and offer insights for others with interest in this same topic. Once completed, findings from this study could extend knowledge about the conduct and measurement of effectiveness in rehabilitation initiatives. If study findings suggest that the intervention is effective, structured active play may become a standard part of rehabilitation.